The realities people live by: A critical reflection on the value of Wolfgang Iser"s concept of repertoire for reading the story of Susanna in the Septuagint - Nolte, S. Philip (HTS teologiese studies, 2013)
The article investigates the value of Wolfgang Iser’s concept of repertoire for reading the apocryphal story of Susanna. The viewpoint is that fictional literature such as the Susanna narrative and reality are not opposites of each other, but that fictional texts tell us something about reality. The investigation will also include Peter L. Berger’s theory on how religion contributes to construct social reality. The study will show that religious texts construct the reality(ies) in which people interact and try to make sense of everyday existence. Two stories contemporary to the writer of the article are employed to show that in a certain sense male perceptions about women have not changed much over two millennia. The critical engagement with the narrative will also ask how Susanna’s story can be interpreted in a responsible and ethical way that is conducive for the constructive development and transformation of individuals and communities.